Prospects for data journalism in Kazakhstan (Herald of Journalism, 2020)
The article discusses the prospects for data journalism in Kazakhstan, the Law «On Access to Information». The authors argue that the only pro- vision of the right of access to information may exist and development of data journalism.
Keywords: Journalism data, data journalism, access to information, the law of the Republic of Kazakhstan.